Anagliptin protects neuronal cells against endogenous amyloid β (Aβ)-induced cytotoxicity and apoptosis. Issue 1 (4th December 2019) - Chen, Zhenbo; Tao, Shanwei; Li, Xiaohui; Zeng, Xudong; Zhang, Mirong; Yao, Qinghe
Abstract: Excessive generation and accumulation of amyloid-β (Aβ) fragments by familial mutations of amyloid precursor protein (APP) and presenilin 1 (PS1) play a key role in causing oxidative stress, mitochondrial abnormalities and neuronal apoptosis in Alzheimer's disease (AD). Anagliptin, a novel DPP-4 inhibitor, is a clinical drug for the management of type II diabetes approved for use in 2012. Little on the pharmacological function of anagliptin against Aβ-induced cytotoxicity in neuronal cells is known. Here, we examined the protective capacities of anagliptin against cytotoxicity in N2a neuronal cells overexpressing APP Swedish mutant and PS1 exon 9 deletion mutant (N2a/Swe.D9). Our results demonstrate that anagliptin reduced the production of ROS and the expression of NADPH oxidase 4 (NOX-4) in N2a/Swe.D9 cells. We also reported that anagliptin activates the antioxidant system by increasing the level of reduced glutathione (GSH) and glutathione peroxidase (GPx) activity. Notably, anagliptin is able to improve mitochondrial function by elevating mitochondrial membrane potential (MMP) and adenosine triphosphate (ATP) production. Additionally, our results demonstrate that anagliptin decreased the vulnerability of cells to hydrogen peroxide (H2 O2 )-induced secondary insult by increasing cell viability and reducing the secretion of lactate dehydrogenase (LDH) and high mobility group box 1 protein (HMGB-1). Importantly, we found that treatment with anagliptin suppressed the mitochondrial-dependent apoptosis pathway by preventing the translocation of cytochrome C, reducing cleavage of caspase-3, and the inhibiting expression of Bax. These results implicate that anagliptin may have potential as a therapeutic agent for AD treatment.